The Role of Information Technology in the Effect of Risk Management on Banking Performance - Rizka Fadilla Rahmawati; Agung Juliarto (JURNAL ECONOMINA, 2026)
Instability in the banking sector can trigger broader economic issues, reduce market valuation, and lead to a loss of public or stakeholder trust. Therefore, it is crucial for banks to continuously monitor the risks they face, even those that are difficult to control. This study aims to provide empirical evidence on the impact of risk management on banking performance (profitability and firm value), with information technology as a moderating variable. The study is based on a sample of banking companies listed on the Indonesia Stock Exchange during the period 2019–2023. Panel data regression models are used to test the hypotheses. Risk management, proxied by capital adequacy (CAR) and climate change initiatives (CCI), has a positive effect on profitability and firm value. Meanwhile, operational inefficiency (BOPO) negatively affects profitability only. The interaction between operational inefficiency and information technology (BOPO_TI) weakens firm value. Risk management through capital adequacy and climate initiatives improves banking performance. However, the weakening effect of IT in the presence of low operational efficiency indicates that technology adoption alone is insufficient. IT implementation must be aligned with operational efficiency and sound risk management to support the ERM objective of "create and protect value".